DEVELOPMENT OF CANNED FISH CURRY - VIJAYAN, P K; BALACHANDRAN, K K (Fishery Technology, 2017)
A process for canning sardine in two different curry media is presented. One curry medium yields a product with medium pungency while the second one has a low pungency. Sardine canned in curry medium having medium pungency developed signs of internal corrosion as well as slight bitter taste at the end of 15 months storage at ambient temperature. Similar phenomenon took place in the other product only at the end of 18 months storage. Being a ready to serve product it needs no further preparation for the table.